1996
DOI: 10.1038/bjc.1996.165
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and localisation of PpIX fluorescence after topical and systemic ALA application, observed in skin and skin tumours of UVB-treated mice

Abstract: SummaryIn this study the kinetics and localisation of protoporphyrin IX (PpIX) fluorescence in skin and skin tumours were examined after topically (20% for 4 h) or systemically (200 mg kg-', i.p.) administered 5-aminolaevulinic acid (ALA). As a model we used hairless mice with skin lesions (actinic keratoses and squamous cell carcinoma), which were induced by daily UVB irradiation. The epidermis of the skin surrounding the tumours (T) was altered (AS); owing to the UVB irradiation, the epidermis was thicker an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 20 publications
2
31
0
1
Order By: Relevance
“…We also showed that PPIX fluorescence kinetics depend on the time of exposure to 5-ALA in cultures of normal bronchial epithelium. PPIX fluorescence kinetics might also depend on the application modalities of 5-ALA [18]. The results of our experiments may better apply to topical application of 5-ALA (for example inhalation of 5-ALA), since the patterns of 5-ALA transport by blood are not taken into consideration in our system.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that PPIX fluorescence kinetics depend on the time of exposure to 5-ALA in cultures of normal bronchial epithelium. PPIX fluorescence kinetics might also depend on the application modalities of 5-ALA [18]. The results of our experiments may better apply to topical application of 5-ALA (for example inhalation of 5-ALA), since the patterns of 5-ALA transport by blood are not taken into consideration in our system.…”
Section: Discussionmentioning
confidence: 99%
“…Six mice were used for identifying visual features of SCCs and nine for in situ PpIX fluorescence examination (17,18). To study the therapeutic efficacy, 24 mice were divided into four groups: untreated, ALA only, light only and PDT.…”
Section: Experimental Designmentioning
confidence: 99%
“…The resulting tissue-specific photosensitization permits photodynamic diagnosis and therapy, whereby far lower light doses are used for diagnosis. Animal studies have demonstrated stronger PpIX fluorescence after application of ALA in colon [8], bladder [9], and skin tumors [10]. ALA can induce strong PpIX fluorescence in tumors of the bronchi, skin, and mammary tissue [7,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The safety of ALA as a topical or systemic photosensitizer has been established in multiple clinical trials [7][8][9][10][11][12][13][14]. PpIX is normally present in tissues of the body.…”
Section: Introductionmentioning
confidence: 99%